Aid and Fiscal Instability - Adam, C; O'Connell, S; Buffie, E (2011)
These two related papers develop a specific aspect of the previous project, how monetary policy choices may require modification when donors and fiscal authorities face credibility problems. Donors would like to commit to continued aid flows and recipients would like to commit to cut public expenditure if aid flows do not materialize. Political factors render both commitments non-credible. These papers use conventional game theoretic approaches to analyse policy implications for the monetary authorities. This work emerges from our joint project and the papers were highly collaborative. They have been brewing for a number of years: my contribution was in the initial conception of the problem. I was less involved in the detailed formalization (O’Connell being the lead game theorist) but the writing of both papers was collaborative.